2016
DOI: 10.1136/bmjopen-2016-013591
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of care home and hospital admissions and their costs for older people with Alzheimer's disease: findings from a large London case register

Abstract: ObjectivesTo examine links between clinical and other characteristics of people with Alzheimer's disease living in the community, likelihood of care home or hospital admission, and associated costs.DesignObservational data extracted from clinical records using natural language processing and Hospital Episode Statistics. Statistical analyses examined effects of cognition, physical health, mental health, sociodemographic factors and living circumstances on risk of admission to care home or hospital over 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 37 publications
7
85
0
Order By: Relevance
“…Attempts were made to comprehensively investigate patient background factors, but eight of these were BPSD. Several studies have indicated that agitation and aggression are risk factors for hospital admission . Patients with dementia can become aggressive, and dementia is associated with significantly increased use of psychotropic medication and injuries .…”
Section: Discussionmentioning
confidence: 99%
“…Attempts were made to comprehensively investigate patient background factors, but eight of these were BPSD. Several studies have indicated that agitation and aggression are risk factors for hospital admission . Patients with dementia can become aggressive, and dementia is associated with significantly increased use of psychotropic medication and injuries .…”
Section: Discussionmentioning
confidence: 99%
“…Since studies have suggested that the annual rate of decline in MMSE score amongst dementia patients is 4–5 MMSE points [24], such an effect estimate is modest, equivalent to an approximately 3-month delay in cognitive decline. However, while the effect sizes are small, they could have a significant impact in terms of costs and hospital or nursing home admissions, which have both been shown to be linked to the level of cognitive function as measured by the MMSE [25]. In addition, the length of time that these benefits continue may be of interest [23].…”
Section: Discussionmentioning
confidence: 99%
“…Family carers provide £8 billion ($11 billion) per annum of unpaid dementia care in the UK and an estimated $522 billion annually in the USA . Family carers are a vital determinant of positive outcomes for people with dementia, for example, having a co‐resident carer predicts lower hospital admission and lower transitions into care homes …”
Section: Introductionmentioning
confidence: 99%